Spotlight - G.T. Van Rooyen 'Materials In Action' Symposium ? Pretoria, 29-30 June 1994 (The Southern African Institute of Mining and Metallurgy, 1994)
Professor G.T. van Rooyen has guided the Department of Materials Science and Metallurgical Engineering at the University of Pretoria in South Africa for the past 32 years. During this period, 54 masters' degrees have been awarded in the Department, and 17 doctorandi promoted. He has also made a major contribution to industry by his incisive analysis, relevant and practical synthesis, and his exceptional talent in innovative design. He is still active in fracture analysis, thermal fatigue, weld simulation transformation kinetics, and fracture mechanics, and continues to contribute to a better understanding of metallurgical problems encountered in practice. He has advised many companies, and has received many honours and recognitions.